2012
DOI: 10.1007/s12088-012-0307-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Screening of Secreted Compounds Produced by the Phase I Variant of Photorhabdus luminescens

Abstract: In this study, antibacterial activity of metabolites secreted by the phase I variant of Photorhabdus luminescens was investigated. Bioactivity of these metabolites was screened against 28 different bacterial species and strains. Bacterial sensitivity was determined by a modified-version of the Kirby-Bauer disk diffusion susceptibility method, whereas the phase I variant's culture permeate was utilized as the "antibacterial" agent. This investigation demonstrates that 11 of the 28 bacterial species tested were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition, Hu et al (2006) also isolated, identified, and chemically synthesized a novel antimicrobial compound, 1,2-isopropyl-5-(3phenyl-oxiranyl)-benzene-1,3-diol (syn. 2-Isopropyl-5-(3phenyl-2-oxiranyl)-1,3-benzenediol) from the larvae of Galleria mellonella infected with the Heterorhabditis megidis Photorhabdus are also known to produce several other SM compounds with broad-spectrum antibiotic properties (McInerney et al, 1991a(McInerney et al, , 1991bMaxwell et al, 1994;Webster et al, 2002;Eleftherianos et al, 2007;Waterfield et al, 2009;Inman and Holmes, 2012;Clarke, 2016). One of them is carbapenem molecule, which is a prominent class of b-lactam antibiotic, which was first identified and characterized by Derzelle et al (2002).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…In addition, Hu et al (2006) also isolated, identified, and chemically synthesized a novel antimicrobial compound, 1,2-isopropyl-5-(3phenyl-oxiranyl)-benzene-1,3-diol (syn. 2-Isopropyl-5-(3phenyl-2-oxiranyl)-1,3-benzenediol) from the larvae of Galleria mellonella infected with the Heterorhabditis megidis Photorhabdus are also known to produce several other SM compounds with broad-spectrum antibiotic properties (McInerney et al, 1991a(McInerney et al, , 1991bMaxwell et al, 1994;Webster et al, 2002;Eleftherianos et al, 2007;Waterfield et al, 2009;Inman and Holmes, 2012;Clarke, 2016). One of them is carbapenem molecule, which is a prominent class of b-lactam antibiotic, which was first identified and characterized by Derzelle et al (2002).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…As the bacterial population reaches stationary phase, production of secondary metabolites, in particular antimicrobials, and an unknown "food signal" is initiated. The secreted antimicrobials are speculated to be a defense mechanism used to ward off competing microbes that may cause the cadaver to putrefy [21,22]. Additionally, researchers suggest that unidentified food signals induce IJs to shed their protective sheaths and continue development to complete their life cycle [23,24].…”
Section: Nematode Biology and Life Cyclementioning
confidence: 99%
“…Photorhabdus are known to produce an array of toxins and secondary metabolites [5,6], and together with their nematode-hosts they are potent insect killers. The Photorhabdus-Heterorhabditis pair provides a tractable genetic model to study animal-microbes relationships [7].…”
Section: Introductionmentioning
confidence: 99%